Malignant Sex Cord-Stromal Tumor, Not Otherwise Specified, Harboring FOXL2, p53, and TERT Promoter Mutations: Report of a Case. (November 2020) - Mayer, Romana; Dandulakis, Mary; Richards, Stephanie; Roque, Dana M.; Staats, Paul N.
Abstract : Rare sex cord-stromal tumors of the ovary cannot be further subclassified and are therefore designated "sex cord-stromal tumor-not otherwise specified." These tumors have highly varied morphology, and the literature describing them is limited. Herein, we report the pathology and clinical course of a 46-yr-old woman diagnosed with sex cord-stromal tumor-not otherwise specified. The tumor was composed predominantly of juvenile granulosa cell tumor histology, with elements of thecoma, adult granulosa, Sertoli, as well as poorly differentiated epithelioid and sarcomatoid components. Next-generation sequencing revealed a FOXL2 C134W mutation, seen most commonly in adult granulosa cell tumors, as well as mutations in TP53 (V172F) and TERT promoter (-124C>T). The patient exhibited an aggressive clinical course involving rapid recurrence with distant metastases that responded to 4 cycles of cisplatin, bleomycin, and etoposide.